ANALISIS UNSUR INTRINSIK PADA CERITA RAKYAT NYI KANIPAH DAN PEMANFAATANNYA SEBAGAI BAHAN PEMBELAJARAN APRESIASI SASTRA DI SMA - Sopyan Sauri; Meliyawati; Lian Nitami; Nia Fadilla Agustin; Bunga Aura Cikal (Direktorat Riset dan Pengabdian pada Masyarakat (DRPM) Universitas Bina Darma, 2025)
This study aims to describe the intrinsic elements of the Nyi Kanipah folktale and its use as a learning material for literary appreciation in high school. The Nyi Kanipah folktale comes from Pandeglang Banten. This study uses a qualitative descriptive method. Data collection techniques are survey techniques, interviews and documentation. The data analysis technique uses the content analysis method with qualitative research steps using the Milles and Hubberman models. The findings of the study are as follows. First, the theme of the folktale is a person's fortitude in living life. Second, the plot is a forward plot. Third, the characters in the story are Nyi Kanipah, Ambu Sair, King Jin and the surrounding community. Fourth, the setting in the folktale is at Nyi Kanipah's house, on the river, the setting is morning, afternoon, evening. and the setting is sad and critical. Fifth, the point of view in the story is third person. Sixth, the message in the folktale is patience that must be applied in living life. The results of the analysis of the intrinsic elements of the Nyi Kanipah folktale can be used as learning material for literary appreciation in high school.